2009
DOI: 10.1111/j.1600-079x.2009.00711.x
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin and serotonin in flowers and fruits of Datura metel L.

Abstract: Datura metel is a plant that contains several different neurologically active phytochemicals which affect human health. On-going research has examined the potential role of the human neuroindoles, melatonin and serotonin, in medicinal plants with neurological efficacy. In this report, we describe the quantification of melatonin and serotonin in flowers and developing fruits of Datura metel and the effects of cold stress on the levels of these neuroindoles in the reproductive tissues of this plant. Melatonin an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
104
1
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 173 publications
(113 citation statements)
references
References 37 publications
5
104
1
3
Order By: Relevance
“…Furthermore, significant increases in melatonin content in seeds were observed as the seeds matured, whereas tryptophan content remained unchanged (Figure 6). Similar findings were also reported in Datura metel, where serotonin and melatonin contents were quite high in the least developed flower buds with their levels progressively decreasing as the flower buds and fruits matured (Murch et al, 2009). Similarly, the highest melatonin content in tomato ) and pepper (Korkmaz et al, 2014) was detected in seedlings and seeds, supporting the notion that higher melatonin content is essential for guarding these tissues from various stresses.…”
Section: Discussionsupporting
confidence: 75%
“…Furthermore, significant increases in melatonin content in seeds were observed as the seeds matured, whereas tryptophan content remained unchanged (Figure 6). Similar findings were also reported in Datura metel, where serotonin and melatonin contents were quite high in the least developed flower buds with their levels progressively decreasing as the flower buds and fruits matured (Murch et al, 2009). Similarly, the highest melatonin content in tomato ) and pepper (Korkmaz et al, 2014) was detected in seedlings and seeds, supporting the notion that higher melatonin content is essential for guarding these tissues from various stresses.…”
Section: Discussionsupporting
confidence: 75%
“…Additional work [29] has shown that, in contrast to the temporal profiles of melatonin and serotonin in tomatoes, the highest levels of these analytes in the herb Datura metel were found in the earliest stages of ovule and fruit development, with sharp declines in concentrations during development resulting in low levels in mature buds and fruit.…”
mentioning
confidence: 99%
“…It is interesting to note that an opposite pattern was observed in fruits of D. metel, as serotonin levels were found to decrease as flowers developed into fruits. Furthermore, cold treatment of buds was found to increase levels of melatonin and serotonin and suggests further that serotonin is especially critical during the early stages of reproductive development in Datura [47] .…”
Section: Reproductive Development and Embryogenesismentioning
confidence: 99%